Pendekatan Integrasi-Interkoneksi dalam Pendidikan PAUD - Muhammad, Najamuddin (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2016)
The aim of this article is describing the Integration-interconnection Paradigm and its implementation in early childhood education, as we know early childhood education is very important in laying the foundation of science, morality and spirituality of children. This integration-interconnection paradigm offers an idea to reduce the tension between the religious sciences and other social sciences. This paradigm affirms that any scientific buildings, both religious science, science can’t stand alone, but require cooperation, mutual correction and interconnectivity, this paradigm also helps people in the face of the complexity of human life.